The association between neonatal head circumference and caesarean section for failure to progress - حسن لؤي (Latakia University Journal -Medical Sciences Series, 2021)
Background: There is global concern about rising caesarean section rates. Identification of risk factors could lead to preventative measures. Aim: To describe the association between neonatal head circumference and both caesarean section for failure to progress and intrapartum caesarean section overall. Materials and Methods: This was a prospective cohort study conducted at Obstetrics and Gynecology Department, Tishreen University Hospital, Lattakia, Syria, during the period between July 2019 – July 2020. The study enrolled 330 women with uncomplicated singleton pregnancies at term gestation (37 weeks or more) with cephalic presentation. Neonatal head circumference was grouped into groups and multiple logistic regressions performed. Results: The rates of caesarean section for failure to progress were 6.5%, 28.3%,30.5%, and 34.7% in successive head circumference groups. Rates of intrapartum caesarean section overall were 8.1%, 28.3%, 35.3% and 28.3%. The odds ratios for caesarean section for failure to progress were: 1, 4 (95% CI 1.1 – 14.5), 4.5 (1.1 - 17) and 5.7 (1.2 – 27.4) for successive head circumference groups after adjusting for multiple demographic and clinical factors. The adjusted odds ratios for intrapartum caesarean section for any indication were: 1, 3.5 (95% CI 1.5 – 8.2), 4.8 (2.1 – 11.3) and 5.1 (2.1–12.2), respectively. Conclusion: There is a strong positive relationship between head circumference groups and both caesarean section for failure to progress and caesarean for any indication. If this finding is confirmed using ultrasound measurements, there is potential for head circumference to be incorporated into predictive models for intrapartum caesarean section with a view to offering interventions to reduce the risk of caesarean section.